Lipopolysaccharide binding protein, interleukin-6 and C-reactive protein in acute gastrointestinal infections: value as biomarkers to reduce unnecessary antibiotic therapy - Elsing, Christoph; Ernst, S.; Kayali, N.; Stremmel, Wolfgang; Harenberg, S. (Infection, 2011)
Several new biomarkers, such as lipopolysaccharide binding protein (LBP) and interleukin-6 (IL-6), have the potential to determine the severity and outcome of infectious diseases. LBP and IL-6 serum levels have not been reported in patients with gastrointestinal infections. The aim of this study was to compare established markers of infection with new markers, such as LBP and IL-6, in patients with acute gastrointestinal infections